Characterization of 60 mm AlN Single Crystal Wafers Grown by the Physical Vapor Transport Method. Issue 16 (18th August 2019) - Wang, Qikun; Lei, Dan; He, Guangdong; Gong, Jianchao; Huang, Jiali; Wu, Jason
Abstract : Physical Vapor Transport Crack‐free bulk AlN single crystals up to 60 mm in diameter are grown for the first time by the physical vapor transport method. The demonstrated entire wafer exhibits excellent ultraviolet transparency with absorption coefficients of 14–21 cm −1 in the range 260–280 nm, and the Raman spectra show an E2(high) FWHM of 2.86 cm −1 . More details can be found in article number1900118 by Qikun Wang, Jason Wu, and co‐workers.